2013
DOI: 10.1001/jamasurg.2013.1048
|View full text |Cite
|
Sign up to set email alerts
|

Expectations for Weight Loss and Willingness to Accept Risk Among Patients Seeking Weight Loss Surgery

Abstract: Importance Weight loss surgery (WLS) has been shown to produce long-term weight loss but is not risk free or universally effective. The weight loss expectations and willingness to undergo perioperative risk among patients seeking WLS remain unknown. Objectives To examine the expectations and motivations of WLS patients and the mortality risks they are willing to undertake and to explore the demographic characteristics, clinical factors, and patient perceptions associated with high weight loss expectations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 27 publications
5
49
0
1
Order By: Relevance
“…Although we have demonstrated that surgery can significantly improve outcomes for the very elderly and comatose, patients will vary in their acceptance of the trade-off against surgical risk [24,25]. The impact on outcomes following surgery reported in recent randomised controlled trials such as DECRA [26] and RESCUEicp [27] have highlighted that patients' opinion on whether a particular surgical outcome is considered as improvement or not will vary.…”
Section: Discussionmentioning
confidence: 90%
“…Although we have demonstrated that surgery can significantly improve outcomes for the very elderly and comatose, patients will vary in their acceptance of the trade-off against surgical risk [24,25]. The impact on outcomes following surgery reported in recent randomised controlled trials such as DECRA [26] and RESCUEicp [27] have highlighted that patients' opinion on whether a particular surgical outcome is considered as improvement or not will vary.…”
Section: Discussionmentioning
confidence: 90%
“…Of those eligible, 654 enrolled, representing a 70 % response rate. Details on recruitment and data collection have been described elsewhere and include an hour-long baseline telephone interview [10]. The study was approved by the institutional review boards at Beth Israel Deaconess Medical Center, Boston Medical Center, and University of Massachusetts.…”
Section: Methodsmentioning
confidence: 99%
“…By using a common metric, the impact of diseases and treatment outcomes can be compared across conditions [9]. In a survey study of over 650 patients seeking bariatric surgery [10], we measured the health utility or the quantifiable value patients placed on their current weight and health. In that study, we identified the two strongest correlates of patients’ utility among the QOL domains measured by the SF-36 and IWQOL-lite were social stigma and obesity’s adverse impact on role or work functioning, suggesting that these were the two most important QOL domains that drove diminished overall well-being or how much patients devalued their current state of being (disutility).…”
Section: Introductionmentioning
confidence: 99%
“…Details of the data collection have been described previously. [12, 14] Of 654 patients who participated, 541 underwent surgery. We previously reported the baseline alcohol use of the 654 patients seeking WLS.…”
Section: Methodsmentioning
confidence: 99%